A Group of Byzantine Metal Crosses Found in Erzurum Archaeology Museum - Demet Okuyucu (Art-Sanat)
A total of ten metal crosses in the Erzurum Archaeology Museum constitute the subject of this study. Six of the artifacts were found around the mound located in the Parmaksız Village of Hınıs District of Erzurum Province, three of them were purchased and one of them was brought to the museum after the soil drilling studies which were carried out during the excavations of Erzurum Castle in 2008. In the introduction, the concept of the cross and its place and importance in Christian theology are discussed. The subject of the study is ten metal crosses in Erzurum Archaeology Museum. First of all, with the permission of the forehead taken from the museum, the artifacts were seen in situ, and their measurements and pictures were taken. Detailed drawings of the crosses made in the computer environment have been added to the catalogue section so that the works can be perceived more clearly. The arrival dates and forms of the artifacts have been presented from the museum records. The works that the article focuses on are grouped as ceremonial-consecrated cross and pendant crosses, and are described and introduced in detail in the catalogue section. A dating proposal is presented in the evaluation section by making comparisons with similar examples belonging to various collections, unearthed in archaeological excavations or recorded in the inventories of museums in various forms and also being the subject of academic writings.As a result of the comparison and evaluation, it has been concluded that the works examined are identified to be the Byzantine crosses which belong to the period of 6th and 13th centuries, except for one work that cannot be dated.